Legal Analysis of Cash Scams on Paylater Limits as a Preliminary Mode of Criminal Activity - Muhammad Nur Al Fatir; Yuliana Yuli Wahyuningsih (Green Publisher Indonesia, 2026)
Advancements in financial technology have simplified transactions through Paylater services, yet they have also created opportunities for misuse, such as the practice of gesek tunai (gestun), which is carried out through fictitious transactions on e-commerce platforms. The purpose of this study is to examine the legal construction of the “unlawful act” element based on criminal law theory and to determine whether gestun practices in Paylater limits can be categorized as an initial modus operandi of criminal offenses. This research employs primary legal sources, including the Indonesian Criminal Code (KUHP), the Electronic Information and Transactions Law (ITE Law), the Anti–Money Laundering Law (Law No. 8 of 2010), OJK Regulation No. 10/POJK.05/2022, Bank Indonesia Regulation No. 11/11/PBI/2009, and relevant court decisions, using a normative juridical methodology through statutory and case approaches. The findings indicate that gestun in Paylater services meets the criteria of an initial modus operandi of criminal conduct because it involves transaction manipulation that may constitute fraud (Article 378 of the KUHP), embezzlement (Article 372 of the KUHP), money laundering (Law No. 8 of 2010), and even continued offenses (Article 64 of the KUHP). According to both monist and dualist theories, this activity is legally prohibited and also violates administrative regulations issued by the Financial Services Authority (OJK) and Bank Indonesia. This study underscores the importance of enhancing public digital literacy and revising criminal law provisions to specifically regulate the misuse of fintech services.